Regioselective Amination or Alkoxylation of Halogenated Amino-, Thio- or Alkoxypyridines via Pyridyne Intermediates - Heinz, Benjamin; Djukanovic, Dimitrije; Siemens, Fiona; Idriess, Mohamed; Martin, Benjamin; Knochel, Paul (Synthesis, 2021)
The treatment of 3-halopyridines (Cl, Br) bearing an R-substituent in position 2 (R = OEt, NEt2, N-piperidyl, or SEt) or in position 5 (R = OMe, OEt, SEt, NMe2, NEt2, or aryl) with KHMDS and an amine at 25 °C for 12 hours in THF provided regioselectively 3- and 4-aminated pyridines in 56–90% yields. The reaction of 3-bromo-2-diethylaminopyridine with various alcohols in the presence of t-BuOK/18-crown-6 in THF at 80 °C for 20–60 hours gave various 4-alkoxy-2-diethylaminopyridines in 61–81% yields. These substitution reactions were proposed to proceed via pyridyne intermediates.
Keywords: potassium bases; pyridines; amination; alkoxylation; pyridynes